'Ghastly marionettes' and the political metaphysics of cognitive liberalism: Anti-behaviourism, language, and the origins of totalitarianism. (February 2020) - Carr, Danielle Judith Zola
While behaviourist psychology had proven its worth to the US military during the Second World War, the 1950s saw behaviourism increasingly associated with a Cold War discourse of 'totalitarianism'. This article considers the argument made in Hannah Arendt's The Origins of Totalitarianism on totalitarianism as a form of behaviourist control. By connecting Arendt's Cold War anti-behaviourism both to its discursive antecedents in a Progressive-era critique of industrial labour, and to contemporaneous attacks on behaviourism, this paper aims to answer two interlocking questions: Why was behaviourism overtaken by cognitivism as the dominant theoretical orientation of psychologists in the 1960s, and what role did the concept of language play in this shift?